The Impact of Corporate Social Responsibility Disclosure on Company Performance - Noval Adib; Muhammad Dimar Alam; Rizky Aditya Nugraha; Helmy Aulia Rachman; Areta Widya Kusumadewi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study expands on the influence of Corporate Social Responsibility disclosure on firm performance, with a particular focus on advertising intensity as a moderating variable. Using a quantitative research approach, we employ multiple linear regression analysis to examine the relationship between financial performance and Corporate Social Responsibility practices. The sample consists of Indonesian public companies listed in the LQ45 index from 2019 to 2022. Our findings reveal that concealing Corporate Social Responsibility has a positive impact on firm performance, highlighting the beneficial effects of transparent Corporate Social Responsibility practices. However, advertising intensity does not moderate the relationship between Corporate Social Responsibility disclosure and firm performance. These results suggest that while disclosing Corporate Social Responsibility itself improves firm performance, the level of advertising intensity does not change this relationship. This study contributes to the understanding of the role of Corporate Social Responsibility in corporate strategy and offers insights for managers and policymakers in emerging markets such as Indonesia. Future research should explore additional moderating variables and expand the analysis to other market contexts to further validate these findings.